Revamped vaccination policy in India, need of the hour - Parida, Swayam Pragyan; Bhatia, Vikas; Alekhya, G. (International Journal of Research in Medical Sciences, 2021)
The unprecedented COVID pandemic has caused catastrophic loss all over the world. India has faced a flabbergasting second COVID wave. The current COVID mutant strain is more virulent and has become a variant of concern (VOC) with its high infectivity rate. The current second wave is more detrimental when compared to the first wave, where its transmissibility is high, affecting the younger generation, and even the mortality rate is high. Currently, there is no specific treatment against COVID-19. The health care workers (HCW’s) have been fighting the pandemic tirelessly since the beginning of the pandemic, and many were affected, and severe loss of HCWs occurred. The only ray of hope in fighting against this deadly virus is vaccination. Studies have shown that COVID vaccination is effective in preventing the severity of the disease. Hence vaccination is now is the need of the hour. COVID vaccination has to be taken rampant with vaccinating every citizen of the country in the current crisis. The government of India should make serious efforts that vaccination is available and accessible to everyone. With every citizen being vaccinated, one can flatten the current wave and also can prevent further outbreaks.